Maternal education influences Australian infants' language experience from six months. (5th September 2018) - Dwyer, Anne; Jones, Caroline; Davis, Chris; Kitamura, Christine; Ching, Teresa Y. C.
Abstract : Disparities in children's early language skills associated with socioeconomic factors have led to many studies examining children's early language environments, but few as yet in the first year of life. This longitudinal study assessed the home language environments of 50 Australian infants, who varied in maternal education (university education, or not). Full‐day audio recordings were collected and analyzed using the LENA system when infants were aged 6–9 months and 12–15 months. Using the device‐specific analysis software, we assessed 12‐h projected counts of (1) adult speech input, (2) conversational interactions, and (3) child vocalizations. At both ages, higher maternal education was associated with higher counts of adult words and conversational turns, but not child vocalizations. The study adds to the literature by demonstrating disparities in the infants' language experience within the first year of life, related to mothers' education, with implications for early intervention and parenting supports.